TEKNOLOGI PEMANTAUAN KUALITAS AIR ONLINE BERBASIS GSM DENGAN METODE SMS DI SUNGAI KAPUAS - Wahjono, Heru Dwi (Center for Environmental Technology, 2010)
Kapuas River is the largest river on the Borneo island and become the source of water for the people of this island. In Pontianak City, Kapuas River is become the source of raw water for the local water company (PDAM). To maintain product quality, PDAM Pontianak always monitor this river water quality. During the dry season or during high water, raw water quality Kapuas river becomes salty. Meanwhile, during the rainy season brings torrential river water from upstream mud and water turned into peat. To monitor water quality changes in the Kapuas river in the intake location, PDAM Pontianak has installed an online and real time water quality monitoring system using GSM technology. This paper discusses the installation process online water quality monitoring system starting from the preparation, determination of the location until the process of testing the system. The results of monitoring by the monitoring system is expected to assist the production department to determine the necessary action if there is a change of quality of raw water Kapuas river.Ã‚Â Keywords: GSM Communication Based Online Monitoring System, Telemetry System, Intake PDAM Pontianak, Multi Probe Digital Sensor, Water Treatment Plant